Author Correction: TRPV1 SUMOylation regulates nociceptive signaling in models of inflammatory pain - Yan Wang (Nature Portfolio, 2018)
In the originally published version of this Article, the affiliation details for Yan Wang, Yingwei Gao, Qi Deng, Yangbo Wang, Tian Zhou, Yingping Wang, Huiqing Liu, Ruining Ma, Jinke Cheng and Yong Li incorrectly omitted ‘Shanghai Jiao Tong University’. This has now been corrected in both the PDF and HTML versions of the Article.’ Furthermore, the Supplementary Information file originally associated with this Article inadvertently omitted Supplementary Figure 9. The error has now been fixed and the corrected version Supplementary Information PDF is available to download from the HTML version of the Article.